From soil to plant: strengthening carrot defenses against Meloidogyne incognita with vermicompost and arbuscular mycorrhizal fungi biofertilizers - Ahamad, Lukman; Bhat, Aashaq Hussain; Kumar, Harendra; Rana, Aasha; Hasan, Md. Nurul; Ahmed, Ishtiaq; Ahmed, Shakoor; Machado, Ricardo A. R.; Ameen, Fuad (Frontiers in Microbiology, 2023)
Introduction Sustainable agricultural practices for controlling crop pests are urgently needed to reduce the reliance on chemical pesticides, which have long-term detrimental effects on ecosystems. In this study, we assessed the effectiveness of arbuscular mycorrhizal fungi (AMF) and vermicompost (Vc) supplementation, alone and in combination, in mitigating the negative impacts of Meloidogyne incognita infestation on carrot (Daucus carota L.) growth, development, and physiology. Methods We measured different plant growth parameters such as plant height and biomass accumulation, several plant physiological parameters such as the levels of photosynthetic pigments, phenolics, and the activity of defense enzymes such as peroxidases and polyphenol oxidases, and evaluated the severity of Meloidogyne incognita nematode infestation on plants treated or not treated with vermicompost (Vc) and/or arbuscular mycorrhizal fungi (AMF). Results Our findings show that M. incognita significantly affects plant growth, biomass accumulation, and photosynthetic pigment and carotenoid content. The incorporation of Vc and AMF into the soil, either individually or in combination, significantly alleviates the negative effects of nematode infestation on carrot plants. This was accompanied by the induction of phenolic compounds and defense enzymes such as peroxidases (+15.65%) and polyphenol oxidases (29.78%), and by a reduction in the severity of nematode infestation on Vc and AMF-treated plants compared to nematode-infested plants. Principal component analysis (PCA) shows significant correlations between various of the studied parameters. In particular, we observed negative correlations between the application of AMF and Vc alone and in combination and disease severity, and positive correlations between plant growth, photosynthetic pigments phenol content, and activity of defense enzymes. Discussion Our study highlights the relevance of cultural practices and beneficial microorganisms for the sustainable and environmentally friendly management of agricultural pests.